Development of an adaptive two-phalanx grip model for robotic manipulators - Bairon, Karassaeyv; Sandugash, Makhanbetova; Murat, Kunelbayev; Yerbol, Temirbekov; Maksat, Akhmetzhanov (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this work is to study the problem of uniform grip at the points of contact of a round or spherical object (fruits and vegetables) with the grip. The research methodology uses pressure sensors mounted on the “fingers” of the handle. At a certain force value in the contact zone, the “fingers” of the handle stop. The grip must create equal forces at the points of contact of all “fingers” for an even grip. To explore these issues, phalangeal graspers adapting to the fetal surface are analyzed here. The flat model shows the general patterns of the relationship between the forces of the “fingers” of the grip and the round object to be grasped. The flat model shows the general patterns of the relationship between the forces of the “fingers” of the grip and the round object to be grasped. We examined the 3D model of this gripper and calculated the parameters of the 3D model. Conclusions and practical consequences are the values of stresses and elastic displacements at the points of the contact lines of the teeth of the 3D models of the gripper and the object being grabbed. The distribution of forces on a flat diagram and the values of von Mises stresses in the 3D model demonstrate a certain similarity in the uniformity of distribution of these parameters. Color scales with the values of the corresponding parameters are also presented; the calculation was carried out using the finite element modeling method in inventor.